Evaluation of the Phytochemical, Antioxidant, Enzyme Inhibition, and Wound Healing Potential of Calotropis gigantea (L.) Dryand: A Source of a Bioactive Medicinal Product - Alafnan, Ahmed; Sridharagatta, Swathi; Saleem, Hammad; Khurshid, Umair; Alamri, Abdulwahab; Ansari, Shabana Yasmeen; Zainal Abidin, Syafiq Asnawi; Ansari, Siddique Akber; Alamri, Abdulhakeem S.; Ahemad, Nafees; Anwar, Sirajudheen (Frontiers in Pharmacology, 2021)
Traditionally, plants of the genus Calotropis have been used to cure various common diseases. The present research work is aimed to explore the chemical and biological characterization of one of the most common species of this genus, i.e., Calotropis gigantea (L.) Dryand, having multiple folklore applications. The ethanolic extract of leaves of C. gigantea was analysed for the phytochemical composition by determining the total bioactive (total phenolic and total flavonoid) contents and UHPLC-MS secondary metabolites analysis. For phytopharmacological evaluation, in-vitro antioxidant (including DPPH, ABTS, FRAP, CUPRAC, phosphomolybdenum, and metal chelation antioxidant assays) activities, enzyme inhibition potential (against AChE, BChE, α-amylase, and tyrosinase enzymes), and in-vivo wound healing potential were determined. The tested extract has shown to contain considerable flavonoids (46.75 mg RE/g extract) and phenolics (33.71 mg GAE/g extract) contents. The plant extract presented considerable antioxidant potential being most active for CUPRAC assays. Secondary metabolite UHPLC-MS characterization, in both the positive and negative ionization modes, indicated the tentative presence of 17 different phytocompounds; mostly derivatives of sesquiterpene, alkaloids, and flavonoids. Similarly, the tested extract exhibited considerable inhibitory effects on tyrosinase (81.72 mg KAE/g extract), while presented weak inhibition ability against other tested enzymes. Moreover, in the case of in-vivo wound healing assays, significant improvement in wound healing was observed in both the tested models at the doses of 0.5 percent w/w (P<0.001) and 2.0 percent w/w (P<0.01) on the 16th day. The outcomes of the present research work suggested that C. gigantea plant extract could be appraised as a potential origin of bioactive molecules having multifunctional medicinal uses.